2019
DOI: 10.2174/1573396315666190917154058
|View full text |Cite
|
Sign up to set email alerts
|

Primary Immunodeficiency and Cancer in Children; A Review of the Literature

Abstract: The life span of patients with primary and secondary immunodeficiencies has increased due to recent advances in diagnostic and therapeutic strategies. Primary immune deficiencies (PIDs) are genetic disorders that predispose patients to frequent infections, autoimmunity and malignancies. Genomic instability due to defective DNA repair processes and other unknown mechanisms in patients with PID leads to an enhanced risk of cancer. PIDs were originally described as rare diseases occurring only in infants and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…Some IEIs result from genomic instability, apoptosis defects, and other abnormalities that predispose to cancer, without necessarily interfering with immune responses (111). However, other PIDs have an increased risk of cancers due to inadequate control by the immune system of oncogenic viruses such as human papillomaviruses (HPVs), human herpes virus 8, and Epstein-Barr virus (EBV).…”
Section: Iei With Increased Susceptibility To Epstein-barr Virus Infection and Malignanciesmentioning
confidence: 99%
“…Some IEIs result from genomic instability, apoptosis defects, and other abnormalities that predispose to cancer, without necessarily interfering with immune responses (111). However, other PIDs have an increased risk of cancers due to inadequate control by the immune system of oncogenic viruses such as human papillomaviruses (HPVs), human herpes virus 8, and Epstein-Barr virus (EBV).…”
Section: Iei With Increased Susceptibility To Epstein-barr Virus Infection and Malignanciesmentioning
confidence: 99%
“…Malignancy is the second most prevalent cause of mortality in patients with IEI, after infection (29). The lifetime risk of cancer in children with IEI is estimated to be 5-25% (30,31), and the relative risk of cancer in patients with IEI is 1.4 to 1.6 times greater than that in the general population (32,33). It has been reported that genomic instability due to defective DNA repair processes, lack of control of chronic inflammation, susceptibility to oncogenic viruses (such as human papillomavirus or Epstein-Barr virus) and other unknown mechanisms increase the risk of malignancies (29,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of host immunity can tilt this balance to favor the virus, allowing its full oncogenic potential. Besides the persistent inflammatory environment caused by EBV viremia and the expression of oncogenic EBV proteins and nucleic acids, there is an inability to kill transformed cells due to defects in cytotoxicity in certain IEI [ 36 ]. In the IEI discussed below, the mechanisms involved in the immunity against EBV are dysfunctional leading to immune dysregulation and malignancies.…”
Section: Inborn Errors Of Immunity (Iei)mentioning
confidence: 99%